Collective modes in quantum Fermi liquid - Tsintsadze, N.L.; Tsintsadze, L.N. (Физика низких температур, 2011)
Landau’s theory of Fermi liquids is generalized by incorporating the de Broglie waves diffraction. A newly derived kinetic equation of the Fermi particles is used to derive a general dispersion relation and the excitation of zero sound is studied. A new mode is found due to the quantum correction. It is shown that the zero sound can exist even in an ideal Fermi gas. We also disclose a new branch of frequency spectrum due to the weak interaction.